Relationship between HbA1c levels and lipid profile in type 2 diabetes mellitus patients at Jambi Hospital - Pare, Filza Ferlina; Ayudia, Esa Indah; Lipinwati (Proceedings Academic Universitas Jambi, 2025)
This analytical cross-sectional study examined the association between glycated hemoglobin (HbA1c) levels and lipid profile parameters in 82 type 2 diabetes mellitus patients at Jambi Hospital during 2024-2025. With Indonesia ranking fifth globally in diabetes prevalence (approximately 19.5 million cases), understanding the relationship between glycemic control and dyslipidemia remains important for preventing cardiovascular complications. HbA1c provides reliable assessment of long-term glycemic control by reflecting average blood glucose levels over 2-3 months, unaffected by short-term fluctuations. Poor glycemic control in type 2 diabetes frequently correlates with elevated total cholesterol, LDL, triglycerides, and decreased HDL. Data collection included HbA1c and lipid profile measurements (total cholesterol, LDL, HDL, triglycerides) from medical records, analyzed using SPSS version 27.0 with Pearson correlation tests. Normality testing revealed HDL and total cholesterol followed normal distribution, while LDL, triglycerides, and HbA1c did not. Correlation analysis demonstrated a significant positive relationship between HbA1c and triglyceride levels (r=0.248, p=0.025), indicating elevated HbA1c associates with increased triglycerides. No significant correlations emerged between HbA1c and HDL (r=0.062, p=0.579) or LDL (r=0.007, p=0.954). A weak positive trend appeared between HbA1c and total cholesterol (r=0.202, p=0.069). Findings confirm most type 2 diabetes patients exhibited poor glycemic control with dyslipidemia. HbA1c serves as an additional indicator for predicting dyslipidemia risk and preventing cardiovascular disease progression in diabetic populations.